Supplementation of coated sodium butyrate relieved weaning stress and reshaped microbial flora in weaned lambs - Zhao, Fangfang; He, Wenhao; Wu, Tianyou; Elmhadi, Mawada; Jiang, Ning; Zhang, Aizhong; Guan, Pengyu (Frontiers in Veterinary Science, 2024)
Weaning is an important period in the growth and development of lambs. Thus, effectively reducing the occurrence of weaning stress is critical for maintaining lamb production. Coated sodium butyrate has been shown to reduce inflammation, promote intestinal health, and maintain homeostasis. However, the application and potential mechanism of coated sodium butyrate in alleviating weaning stress in lambs are still unclear. To evaluate the effects of coated sodium butyrate on the growth performance, antioxidant capacity, and gut microbiota of weaned lambs, 10 weaned lambs of 21-day-old were randomly divided into two groups: the CON group (basal diet) and the NaB group (basal diet +3 g/kg of coated sodium butyrate). The trial lasted 21 days. The experimental results showed that compared to the CON group, coated sodium butyrate supplementation in the diet significantly increased the average daily weight gain and daily feed intake of lambs (p < 0.05). In addition, compared to the CON group, the addition of coated sodium butyrate also significantly decreased the serum MDA level of lambs (p < 0.05). Notably, the addition of coated sodium butyrate did not have a significant effect on the cecal microbiota, while increasing the diversity of colonic microbiota and promoting the abundance of Lachnospiraceae, Verrucomicrobiota, Akkermansia, Roseburia, and Sinobacteraceae, which are associated with the nutrient absorption of lambs (p < 0.05). These results indicate that dietary supplementation with coated sodium butyrate could promote the growth and antioxidant capacity of weaned lambs and alleviate weaning stress.